The role of aerobic capacity in high-intensity intermittent efforts in ice-hockey - Stanula, A.; Roczniok, R.; Maszczyk, A.; Pietraszewski, P.; Zajac, A. (Biology of Sport, 2014)
The primary objective of this study was to determine a relationship between aerobic capacity ( VO2max) and fatigue from high-intensity skating in elite male hockey players. The subjects were twenty-four male members of the senior national ice hockey team of Poland who played the position of forward or defence. Each subject completed an on-ice Repeated-Skate Sprint test (RSS) consisting of 6 timed 89-m sprints, with 30 s of rest between subsequent efforts, and an incremental test on a cycle ergometer in the laboratory, the aim of which was to establish their maximal oxygen uptake ( VO2max). The analysis of variance showed that each next repetition in the 6x89 m test was significantly longer than the previous one (F5,138=53.33, p<0.001). An analysis of the fatigue index (FI) calculated from the times recorded for subsequent repetitions showed that the value of the FI increased with subsequent repetitions, reaching its maximum between repetitions 5 and 6 (3.10±1.16%). The total FI was 13.77±1.74%. The coefficient of correlation between VO2max and the total FI for 6 sprints on the distance of 89 m (r =-0.584) was significant (p=0.003). The variance in the index of players` fatigue in the 6x89 m test accounted for 34% of the variance in VO2max. The 6x89 m test proposed in this study offers a high test-retest correlation coefficient (r=0.78). Even though the test is criticized for being too exhaustive and thereby for producing highly variable results it still seems that it was well selected for repeated sprint ability testing in hockey players.